دراسة مدى تأثير فجوة الطاقة والحرارة على كفاءة الخلية الشمسية وتأثيرتركيز Ga)) في تركيبCu(In1−xGax)Se2 على كل من فجوة الطاقة وتقارب الإلكترون - نجاح أحمد الزعلوك, (African Journal of Advanced Pure and Applied Sciences, 2024)
Computer simulation and modeling were conducted to study the effect of the widening of the energy gap of the absorbent layer on the efficiency of solar cells to obtain the highest amount of electrical energy. The optimal value of the energy gap at which the solar cell has the highest efficiency was determined and it was found to be equal to (1.1 MeV) at a temperature of (K). 5800) and the maximum efficiency of the solar cell was 0.44. Computer simulations were also conducted to study the effect of the sun's heat on the maximum efficiency of the solar cell, which was found to decrease as the temperature of the sun increases, which necessitates adjusting the design according to different climatic conditions. It was also shown that the value of the optimal energy gap remains constant as the temperature increases. The effect of the concentration ratio of germanium (Ga) in the composition of Cu(In1−xGax)Se2 for the copper indium gallium selenide (CIGS) solar cell was also studied on the energy gap and electron affinity, and the concentration ratio that corresponds to the optimal energy gap was determined. The results showed that the energy gap increases with increasing percentage ((Ga) in the synthesis of Cu(In1−xGax) Se2, and it was found that to obtain an optimal energy gap equal to (eV 1.1) the ratio The appropriate Ga concentration was 0.14, and the simulation was done using MATH-lab, and the obtained results were discussed and interpreted.